Effect of Low-Molecular-Weight Organic Acids on Migration Characteristics of Pb in Reclaimed Soil - Zheng, Yonghong; Li, Yating; Zhang, Zhiguo; Tan, Yuning; Cai, Weiqing; Ma, Chengnan; Chen, Fangling; Lu, Jiangwei (Frontiers in Chemistry, 2022)
The effect of low-molecular-weight organic acids (citric acid and malic acid) on the migration characteristics of Pb in contaminated soils was explored in this study. Reclaimed soil was collected from the coal gangue hill area of the Panyi mine in Huainan City (China). The effect of citric acid and malic acid on the form of Pb present in the reclaimed soil was analyzed by spiking soil samples and simulating Pb-contaminated soil. The results indicate the following. 1) With increased concentration of exogenous Pb, the activity of Pb in the reclaimed soil was effectively improved. 2) The addition of citric acid and malic acid both resulted in an increased fraction of exchangeable Pb in the soil, which effectively promoted the active Pb fraction. As the concentrations of citric acid and malic acid increased, the active Pb fraction of the reclaimed soil increased accordingly. The Pb activation effect of citric acid was observed to be greater than that of malic acid. 3) With extended soil aging time, the activation effect of organic acids on Pb weakened, with the loosely bound Pb gradually transforming into strongly bound Pb. Chelating agents can activate heavy metals in soil, mainly through the combination of chelating agents and heavy metal ions in the soil solution to form soluble metal chelates, so as to increase the bioavailability of heavy metals in soil to plant roots. Therefore, adding citric acid can be considered as a strategy to enhance the efficiency of reclaimed soil remediation because of the ability of Pb activation.